1997
DOI: 10.1051/animres:19970505
|View full text |Cite
|
Sign up to set email alerts
|

Effet de la photopériode sur la production, la composition du lait et sur les consommations volontaires chez la brebis laitière

Abstract: Summary -Effect of photoperiod on milk yield, milk composition and voluntary food intake in lactating dairy ewes. Thirty-eight dairy ewes of the Sarda breed were divided in two groups which were equilibrated for zootechnical criteria. They were subjected to artificially controlled photoperiods of either long daylight (JL: 15h30 (-37.7%) over the same period. The milk solid concentration from the JL ewes (fig 4) was less than that of the JC ewes. The maximum differences, which occurred between days 30 to 40,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 1 publication
4
13
0
1
Order By: Relevance
“…Studies involving ovariectomized ewes also demonstrated that the alternation between periods of LD and SHD (or melatonin treatment mimicking SHD) induced sexual activity after about 50 to 80 d of exposure to SHD (Karsch et al, 1986;Malpaux et al, 1988a;Ravault and Thimonier, 1988). Besides the alternation between SHD and LD, the duration of the light sequences (120 d in the present experiment) could have contributed to the initiation of sexual activity via the development of photorefractoriness, as observed in ewe after 100 to 150 d of exposure to the same and constant photoperiodic signal by some authors (Karsch et al, 1986;Malpaux et al, 1988b;Bocquier et al, 1997).…”
Section: Performance Of Ewes Under the Photoperiod Regimensupporting
confidence: 54%
See 1 more Smart Citation
“…Studies involving ovariectomized ewes also demonstrated that the alternation between periods of LD and SHD (or melatonin treatment mimicking SHD) induced sexual activity after about 50 to 80 d of exposure to SHD (Karsch et al, 1986;Malpaux et al, 1988a;Ravault and Thimonier, 1988). Besides the alternation between SHD and LD, the duration of the light sequences (120 d in the present experiment) could have contributed to the initiation of sexual activity via the development of photorefractoriness, as observed in ewe after 100 to 150 d of exposure to the same and constant photoperiodic signal by some authors (Karsch et al, 1986;Malpaux et al, 1988b;Bocquier et al, 1997).…”
Section: Performance Of Ewes Under the Photoperiod Regimensupporting
confidence: 54%
“…Each group under controlled photoperiod was exposed to the same light regimen, but the LD and SHD sequences were staggered by 2 mo to spread mating periods throughout the year Photoperiod to control sheep reproduction ( Figure 1). The duration of the photoperiod sequences was fixed at 120 d because the development of refractoriness to the same and constant photoperiodic signal (SHD or LD) was expected to occur after 100 to 150 d of exposure to constant day length (Karsch et al, 1986;Malpaux et al, 1988b;Bocquier et al, 1997). Based on previous study by Chemineau et al (1988) reporting that sequences of 3 mo of LD and SHD stimulates estrous activity about 50 d after the transition to SHD, the breeding period began 55 d after the start of the SHD for a duration of 35 d. In a view of practical application of the photoperiod schedule in an accelerated lambing system, and to reduce unproductive period, nonpregnant ewes at ultrasound scanning were treated with an intravaginal progestagen sponge (Veramix, Upjohn, Orangeville, Canada) for 14 d. At sponge withdrawal, ewes were injected with 450 IU of eCG (Folligon, Intervet, Whitby, Canada), transferred in SHD and introduced, 48 h later, in the following photoperiod group in mating (transfer of these ewes is represented by arrows in Figure 1).…”
Section: Treatmentsmentioning
confidence: 99%
“…In Mediterranean areas, ewe lactation generally occurs in the period when days are lengthening. In dairy ewes, an increase in the hours of light seemed to increase milk production and feed intake (Bocquier et al, 1997). This effect was evident when the treatment lasted more than 30 days and may be explained by the fact that animals fed more when there was more light.…”
Section: Lambing Season Parity and Type Of Lambingmentioning
confidence: 98%
“…Long day length has been shown to stimulate milk production during lactation but to impair milk fat in cattle (Peters et al, 1978 and1981;Stanisiewsky et al, 1985;Dahl et al, 2000 andPetitclerc, 2003), sheep (Bocquier et al, 1984(Bocquier et al, , 1990(Bocquier et al, and 1997 and goats . In contrast, short days, when applied during lactation, have a negative effect on milk production per se but increase the fat and protein contents of milk.…”
Section: Seasonality Of Reproductive Activity Is An Old Story First Smentioning
confidence: 99%